Bioactivities of decoctions from Plectranthus species related to their traditional use on the treatment of digestive problems and alcohol intoxication. (28th June 2018) - Brito, Elsa; Gomes, Emma; Falé, Pedro L.; Borges, Carlos; Pacheco, Rita; Teixeira, Vitor; Machuqueiro, Miguel; Ascensão, Lia; Serralheiro, Maria Luisa M.
Abstract: Ethnopharmacological relevance: Decoctions of Plectranthus species are traditionally ingested after large meals for treatment of food digestion and alcohol abuse. Aim of the study: This study aims at associating the digestion-related ethno-uses of Plectranthus species decoctions to molecular mechanism that might explain them: easing digestion (AChE inhibition) and treating hangover (ADH inhibition) Material and methods: Decoctions from Plectranthus species were analysed for their alcohol dehydrogenase (ADH) inhibition and acetylcholinesterase (AChE) inhibition, related with alcohol metabolism and intestinal motility, respectively. Identification of the active components was carried out by LC-MS/MS and the docking studies were performed with AChE and the bioactive molecules detected. Results: All decoctions inhibited ADH activity. This inhibition was correlated with their rosmarinic acid (RA) content, which showed an IC50 value of 19 μg/mL, similar to the reference inhibitor CuCl2 . The presence of RA also leads to most decoctions showing AChE inhibiting capacity. P. zuluensis decoction with an IC50 of 80 μg/mL presented also medioresinol, an even better inhibitor of AChE, as indicated by molecular docking studies. Furthermore, all decoctions tested showed no toxicity towards two human cell lines, and a high capacity to quench free radicals (DPPH), which also play a helpful in the digestive process, related with their RA content. Conclusions: All activities presented by the RA-rich Plectranthus decoctions support their use in treating digestion disorders and P. barbatus could explain its use also for alleviating hangover symptoms. Medioresinol, which is present in P. zuluensis, exhibited a significant AChE inhibition and may provide, in the future, a new lead for bioactive compounds. Graphical abstract: